Tourist's Satisfaction in Terms of Accommodation: A Case Study in Vlore, Albania. Issue 1 (January 2020) - Pjero (Beqiraj), Elenica; Gjermëni, Orgeta
Abstract: This study aims to explore tourist's satisfaction on the accommodation provided during their stay in Vlore (Albania) touristic structures, and if there are possible associations between different characteristics related to this service and tourists. Lack of studies on analyzing customer satisfaction in the industry of accommodation, especially for Vlore, have prompted us to undertake this study. The study results are important for local government, the accommodation industry, and is a source of information for whom is interested to improve their accommodation services, or to invest in accommodation industry located in Vlore, Albania. "Netnography" is used to collect data for our research purpose from the reviews in TripAdvisor website. Using descriptive and inferential statistics, this study concludes that 64.9 percent of the ratings are "very good" or "excellent, " regardless of the accommodation structure chosen. Accommodation structures should have a clear defined idea of what kind of tourist they want to attract in a certain period of the year, in order to offer the quality tourists expect. Furthermore, understanding of tourist satisfaction evaluation is important in implementing successful marketing campaigns.